Failure and prospect : Lazarus and the rich man (Luke 16:19-31) in the context of Luke-Acts /: Lazarus and the rich man (Luke 16:19-31) in the context of Luke-Acts. ([2019]) - Bredenhof, Reuben
No abstract available